2018
DOI: 10.3892/mco.2018.1604
|View full text |Cite
|
Sign up to set email alerts
|

18F‑fluorodeoxyglucose imaging of primary malignant pericardial mesothelioma with concurrent pericardial and pleural effusions and bone metastasis: A case report

Abstract: Primary malignant pericardial mesothelioma (PMPM) is an aggressive tumor that originates from the mesothelial cells of the pericardium. PMPM with extensive atrial infiltration and bone metastasis is extremely rare. The diagnosis and staging of PMPM based on anatomical imaging may be difficult when concurrent pericardial and pleural effusions are present. A 28-year-old man presented with progressive chest pain. Concurrent pericardial and pleural effusions were identified on computed tomography. On echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, in a review of 103 published PPM cases, it was found that chemotherapy, but not surgery, provided a statistically significant survival benefit. Of note, a doublet regimen, cisplatin plus pemetrexed, was used as the first-line treatment in almost all reported cases with chemotherapy ( 6 , 7 , 9 11 , 17 , 18 , 20 , 21 ). In only one reported case ( 14 ), a combination of bevacizumab, cisplatin, and pemetrexed was used as the first-line treatment for PPM, but unfortunately, the tumor remained stable after eight cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in a review of 103 published PPM cases, it was found that chemotherapy, but not surgery, provided a statistically significant survival benefit. Of note, a doublet regimen, cisplatin plus pemetrexed, was used as the first-line treatment in almost all reported cases with chemotherapy ( 6 , 7 , 9 11 , 17 , 18 , 20 , 21 ). In only one reported case ( 14 ), a combination of bevacizumab, cisplatin, and pemetrexed was used as the first-line treatment for PPM, but unfortunately, the tumor remained stable after eight cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is no consensus on the treatment of PPM, although the survival benefit of chemotherapy has been shown to be superior to that of surgery ( 6 ). In almost all reported cases with chemotherapy, a doublet regimen, cisplatin plus pemetrexed, was used as the first-line treatment ( 6 , 7 , 9 11 , 17 , 18 , 20 , 21 ). Here we present a case of early diagnosis of PPM promoted by the indication of the patient's occupational asbestos exposure history and clinical presentations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations